The Effectiveness of a Pocket Book as an Educational Medium in Increasing Knowledge of Diabetes Mellitus Prevention Among Students of SMAN 1 Meulaboh, West Aceh Regency - Zilvia Zuhra; Lili Eky Nursia N; Meutia Paradiba; Fikri Faidul Jihad; Mardi Fadillah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Background: The World Health Organization (WHO) reported in 2021 that 537 million (10.5%) adults (20-79 years old) had diabetes. In 2024, in West Aceh Regency, Johan Pahlawan District, 748 cases of Diabetes Mellitus were found. Diabetes Mellitus is a non communicable disease whose prevalence is increasing, including in the adolescent age group. Adolescents are a group that is vulnerable to lifestyle changes that can increase the risk of developing Diabetes Mellitus. Therefore, education about the prevention and management of Diabetes Mellitus in adolescents is very important to be carried out from an early age. This research has high urgency in the context of public health, especially in the prevention and management of Diabetes Mellitus in adolescents, because it can provide effective solutions through pocket books as a simple, concise, and easy to carry educational medium. Objective: Research to determine the effectiveness of pocket books as educational media in increasing adolescent knowledge about Diabetes Mellitus. Methods: This study used a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 38 students in 10 th grade. The sample size was 38 students, selected using purposive sampling technique with criteria of age 14-15 years. The research instrument was a validated questionnaire on knowledge about Diabetes Mellitus. Data analysis was performed using paired sample t-test with a significance level 0f 0.05. Results: The mean difference in scores was -30,395 with a standard deviation of 8,086. The 95% confidence interval ranged from -33,052 to -27,737. The t-test value obtained was -23.172, and the significance value was 0.000 (p<0.05). This indicates that there is a significant difference between the pretest and post-test scores. And the N-gaiin test had a mean value of 0.7692 > 0,7 which means the effectiveness is high, and the N-gain percentage showed a mean value of 76.9236 or 77.1%, indicating that it is effective. Conclusion: Education through pocket books has been proven effective in improving adolescents knowledge about diabetes melitus, making it a practical and easily understandable alternative medium for health promotion.